2020
DOI: 10.1007/s40519-020-00864-0
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis paper: electroacupuncture targeting the gut–brain axis to modulate neurocognitive determinants of eating behavior—toward a proof of concept in the obese minipig model

Abstract: Acupuncture has thousands of years of history and perspective for the treatment of many health problems and disorders. Beneficial effects of acupuncture on obesity have been demonstrated at various levels in animals and clinical trials, with almost no adverse effect, even when combined with local electrical stimulation, i.e., electroacupuncture (EA), a way to potentiate the effects of acupuncture. However, there is still scattered evidence about the impact of EA on brain functions related to the control of eat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 100 publications
(154 reference statements)
0
10
0
Order By: Relevance
“…This study is the first to implement electroacupuncture (EA) in the minipig model with the aim of modulating gut-brain signals and the BOLD fMRI hemodynamic responses in brain regions involved in food intake control, pleasure, and motivation. In a previously published hypothesis paper [ 1 ], we identified three acupoint combinations likely to have an effect on the gut-brain axis, including changes in the autonomic nervous system and especially the sympathovagal balance, as well as of hunger and satiety plasma markers. The present princeps study demonstrated that acute EA on specific acupoints significantly modulated several of these physiological and metabolic parameters compared to basal, sham, and/or control stimulation, with contrasting effects in terms of BOLD responses in brain regions involved in the hedonic and cognitive control of food intake.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study is the first to implement electroacupuncture (EA) in the minipig model with the aim of modulating gut-brain signals and the BOLD fMRI hemodynamic responses in brain regions involved in food intake control, pleasure, and motivation. In a previously published hypothesis paper [ 1 ], we identified three acupoint combinations likely to have an effect on the gut-brain axis, including changes in the autonomic nervous system and especially the sympathovagal balance, as well as of hunger and satiety plasma markers. The present princeps study demonstrated that acute EA on specific acupoints significantly modulated several of these physiological and metabolic parameters compared to basal, sham, and/or control stimulation, with contrasting effects in terms of BOLD responses in brain regions involved in the hedonic and cognitive control of food intake.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional acupuncture and one of its modern derivatives, electroacupuncture (EA), are increasingly used for treating various diseases and especially gastrointestinal disorders [ 1 , 2 ]. Acupuncture and EA are usually appreciated for their limited adverse effects and good clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, we found no study aimed at investigating the effects of acupuncture or EA in a pig model of obesity or hyperphagia (an abnormally strong sensation of hunger or desire to eat often leading to or accompanied by overeating) nor in any other large animal model, which highlights the complete lack or research in this promising field. We recently published a hypothesis study [ 178 ] presenting the rationale and a methodological approach to investigate the effects of electroacupuncture in obese minipigs. This ongoing study is the first of its kind.…”
Section: Large Animal Models Of Obesity and Acupuncture/electroacupuncturementioning
confidence: 99%